2021
DOI: 10.3390/nano11123450
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Cu Spin Fluctuations in High-Tc Cuprate Superconductor Nanoparticles Investigated by Muon Spin Relaxation

Abstract: The nano-size effects of high-Tc cuprate superconductor La2−xSrxCuO4 with x = 0.20 are investigated using X-ray diffractometry, Transmission electron microscopy, and muon-spin relaxation (μSR). It is investigated whether an increase in the bond distance of Cu and O atoms in the conducting layer compared to those of the bulk state might affect its physical and magnetic properties. The μSR measurements revealed the slowing down of Cu spin fluctuations in La2−xSrxCuO4 nanoparticles, indicating the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…The smaller the crystallite size, the stronger the magnetism, which means the magnetic correlation is more developed in the smaller sample. 28 It is confirmed that reducing the particle size down to nanometer sizes causes the suppression of superconductivity while strengthening the magnetism of the electron-doped cuprate superconductors. This result could suggest that there might be a competition between superconducting and magnetic states induced by nano-size effects.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The smaller the crystallite size, the stronger the magnetism, which means the magnetic correlation is more developed in the smaller sample. 28 It is confirmed that reducing the particle size down to nanometer sizes causes the suppression of superconductivity while strengthening the magnetism of the electron-doped cuprate superconductors. This result could suggest that there might be a competition between superconducting and magnetic states induced by nano-size effects.…”
Section: Resultsmentioning
confidence: 92%
“…These results indicate that the crystallite size can be designed by controlling the sintering and annealing temperature. 28,39 Moreover, sintering temperature plays a more important role than annealing temperature to make a bigger crystallite size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inelastic neutron scattering studies, on Pr La Ce CuO [ 49 ] and similar electron-doped compounds [ 50 ], have revealed that high energy spin excitation of such compounds are similar to those observed in anti-ferromagnetic alloys. Moreover, observations of Cu spin-fluctuations have been proved by muon spin relaxation experiments in cuprate superconductors [ 51 ]. In this respect, Rivier and Zlatic developed a model describing the resistivity of itinerant electrons scattered by localized anti-ferromagnetic spin fluctuations [ 52 ] where a linear scaling-law for the resistivity only occurs up to the so-called spin-fluctuation temperature .…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, two articles in this Special Issue are dedicated to some interesting interrelations between magnetic and superconducting orders that become realizable through nanoscience. Winarsih et al [ 6 ] conducted studies of nanoparticles of the La Sr CuO cuprate superconductor, observing that a reduction of the particle size down to the nanometric scale is accompanied by the appearance of magnetic correlation in the Cu spin fluctuations. They likewise observed a change in the bond distance between Cu and O ions in the conducting layer, which seems to correlate with that new magnetism.…”
mentioning
confidence: 99%